Health Care and Human Rights after Auton and Chaoulli - Cousins, Mel (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractThe judicial interpretation of the entitlement to health care under the Charter and human rights legislation has tended to swing between interventionist and non-interventionist poles. In Eldridge, the Supreme Court of Canada held that a failure to provide sign language interpretation where this was necessary to ensure equal access to health care was in breach of the equality provisions of the Charter. However, in a subsequent case, Auton, the Court narrowly circumscribed the limits of this approach, holding that the Canadian system of public health care was, by its very terms, a partial health plan. It followed that exclusion of particular non-core services could not, in itself, be seen as less favourable treatment.The Chaoulli decision marked a return to a more interventionist approach with the Court holding (by a narrow majority) that the prohibition on private health insurance provided for in Quebec law was inconsistent with section 1 of the Quebec Charter. This judgment has been cited in over eighty decisions of courts and tribunals. However, just how important has Chaoulli been in terms of the overall approach of the Canadian courts?The author suggests that Chaoulli—despite its significance in the legislative arena—has had a somewhat limited impact to date on the case law concerning health care, and that Auton has clearly had a greater impact to date. The author examines several examples from subsequent case law that point to the weakness of the approaches taken in both Auton and Chaoulli. The narrow approach adopted in Auton can lead to equality claims being dismissed without any proper discrimination analysis and shows the manner in which a broad use of the “benefit provided by law” requirement may weaken equality jurisprudence. Conversely, the case law highlights the fact that the courts will have to reject much more difficult claims than those upheld in Chaoulli unless they wish to develop positive obligations under section 7 of the Charter.